Pengaruh Kompensasi Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Studi Pada CV. Cahya Makmur Furniture Jakarta Barat - Muhammad Rizky Fathoni; Irfan Rizka Akbar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
CV. Cahya Makmur Furniture Jakarta Barat needs to have excellent human resources in order to increase business productivity in the furniture sector so that it can survive in a highly competitive market. This study aims to analyze the influence of compensation and non-physical work environment on employee performance at CV. Cahya Makmur Furniture Jakarta Barat, both partially and simultaneously. The method used is quantitative with a saturated sampling technique on 55 respondents. Data was collected through questionnaires and analyzed using validity tests, reliability tests, classical assumptions, regression, correlation, determination, and hypothesis testing with the assistance of SPSS version 27. The results of the study indicate that compensation has a positive and significant impact on employee performance. The non-physical work environment was also found to have a positive and significant impact on performance. Simultaneously, compensation and the non-physical work environment have a significant impact on employee performance.